Comportamento de busca e obtenção de informações na gestão de materiais, no âmbito da administração pública do Poder Executivo do Estado de Minas Gerais: um estudo comparativo - Almeida, Betânia Lourenço Silva de (2007)
The present paper is inserted in the context of information management and brings a study about search and gathering of information by the supply managers of Public Administration in Minas Gerais Executive Power, This paper is based on bibliographic search, combined with field search with the participation of 21 supply managers, who wore arguied by means of a questionary, This study reveals that the supply managers of private organizations give more value to the information in their function and have more success in its acquisition, as they dispose of better information sources. In the Public Administration of Minas Gerais Executive Power, these managers work at more developed organizations in terms of information management and institutional performance analyses. The supply administrators of autarquias and public foundations still need considerable development in the areas of information management as they have the worst performance. The secretary managers have a median performance, however, it has to be noted that the frequency of information search by these managers is incompatible with lhe very nature of their attributions as managers. So, we can conclude that measures to professional improvement must be taken by the secretaries, autarquias and public foundations. The paper reinforces the value of better information sources for the supply management in the secretaries, autarquias and foundations. In this context, the Si AD/MG is an adequate information source about buying activity that, nevertheless, needs improvement in information display of contractual obligations by materials suppliers. At the end, the paper put in doubt the efficiency of SI AD/MG as the unique system of information for all Public Administration of Minas Gerais Executive Power.